2022
DOI: 10.1017/s0007114522001192
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationship between food insecurity and weight status in Brazil

Abstract: Obesity and undernutrition are manifestations of malnutrition that affect many people worldwide. A lack of access to food may explain the association of food insecurity (FI) with both undernutrition and obesity, but there are other factors that are specifically related to obesity. Studies have also found that FI is related to both overweight and obesity among women but not among men. The present study aimed to evaluate the association between FI and weight status among adults from a nationally representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In particular, the association between food insecurity and obesity has shown mixed findings by age and gender. This association appears not to be present in older men even though food insecurity and obesity coexist among low-income, older women due to differences in household income, educational attainment, and social networks (73)(74)(75)(76)(77).…”
Section: Food Insecurity and Obesity In Older Adultsmentioning
confidence: 98%
“…In particular, the association between food insecurity and obesity has shown mixed findings by age and gender. This association appears not to be present in older men even though food insecurity and obesity coexist among low-income, older women due to differences in household income, educational attainment, and social networks (73)(74)(75)(76)(77).…”
Section: Food Insecurity and Obesity In Older Adultsmentioning
confidence: 98%
“…The analyses describe the population on sociodemographic characteristics, including information about self-reported sex (men; woman), age (20-29.9; 30-39.9; 40-49.9; 50-59.9), years of schooling (≤4, 5-8, ≥9) and geographical region (North, Northeast, Southeast, South, Midwest). These variables were selected and categorized based on a previous study using the same study population, which observed a significant relationship between education level and place of residence (geographical region and place of households) with overweight [3] and food intake [25].…”
Section: Assessment Of Household Food Insecuritymentioning
confidence: 99%
“…In Brazil, data from the last National Health Survey showed the presence of high rates of obesity in the adult population (25.9%), with a higher prevalence of obesity among women (29,5%) than among men (21.8%) [1]. Additionally, studies demonstrate the increase of overweight and obesity in low-income populations [2], and among those living in household with Food Insecurity (FI) in Brazil [3,4].…”
Section: Introductionmentioning
confidence: 99%